Crowds and Speculation: A study of crowd phenomena in the U.S. financial markets 1890 to 1940 - Kristian Bondo Hansen (Copenhagen Business School (CBS), 2017)
This dissertation undertakes an explorative historical analysis of problems associated with crowd phenomena in the U.S. financial markets between 1890 and 1940. While a study of crowd-related problems in the financial markets invariably involves examinations of panics and crises, the dissertation shows that crowds were not exclusively seen as crisis phenomena, but were considered by many financial writers to be of much broader significance to the organisation and functioning of markets. The dissertation claims that it is necessary to explore the close connections between financial markets and crowd phenomena in order to fully understand how markets were perceived and conceptualised in the given historical period. Inspired by Michel Foucault's reflections on the analysis of problematisations, the dissertation explores how practical, academic and popular accounts of financial markets problematised (i.e. reflected upon, contested and responded to) various crowd phenomena as they occurred in the markets. As part of the historical exposition, the dissertation examines how financial writers employed tropes and terminology from late nineteenth century crowd theories when describing and seeking to explain the processes and practices of the markets. The dissertation argues that the way in which crowd phenomena were problematised as well as the attempts to address these alleged crowd problems influenced perceptions of financial markets and transformed approaches to market analysis and speculation. Drawing on an archive of handbooks on how to become a successful investor or speculator, scholarly work on financial markets (from the academic fields of economics, sociology and psychology) as well as a range of popular (fictional and non-fictional) textual accounts of trading in financial markets, the dissertation offers a broad, yet rigorously focused, historical perspective on crowd phenomena in financial markets. Furthermore, it explores how ideas about crowd action, imitation, herding and contagion were introduced to and became integral parts of the discourses on financial markets. Reiterations of such historically formed ideas about crowd phenomena in financial markets are still prominent in current discussions and the dissertation thus offers a historical contextualisation of a pertinent feature of contemporary debates on financial markets.
hdl:10398/9496
Keywords: 650